Chemistry Studentsâ€™ Understanding of Lewis Structure, VSEPR Theory, Molecular Geometry, and Symmetry: A Cross-Sectional Study - Habiddin, Habiddin; Farizka, Lilla; Shuid, Ahmad Naqib bin (Jurnal Tadris Kimiya, 2023)
Most chemical concepts are abstract, hierarchical, and constructed from basic to complex concepts. Lewis structure, VSEPR theory, molecular geometry, and molecular symmetry have hierarchical idea. This study attempted to characterize and determine the relationship between studentsâ€™ knowledge of Lewis structure, VSEPR theory, molecular geometry, and molecular symmetry of the 1st, 2nd, and 3rd-year chemistry students at a public university. This study involved 88 students in total selected using proportionate stratified random sampling. The instrument was a relevant short-answer question on the three topics. The data were measured using nonparametric statistics, especially the Kruskal-Wallis difference and Spearman Rank correlation tests.Â  This studyâ€™s results show differences in understanding of Lewis structure, molecular geometry, and symmetry between the 1st, 2nd, and 3rd-years students. The 3rd-year students always performed better than the 1st and 2nd-year students for all topics. The test result confirms a positive and strong relationship between studentsâ€™ understanding of Lewis structure and molecular geometry for the three groups of students with Ï values of 0.979, 0.979, and 0.966 (< 0.01) for 1st, 2nd, and 3rd-year students, respectively.